Analysis of Potential Export Market Strategy in Craft Business from Typical Karo Woven Cloth in North Sumatra - Situmorang, Katherine; Sawitri, Dewi Khrisna (Journal of Business Management and Economic Development, 2024)
Export market research is an important component in carrying out export activities. In this research, an analysis of export market opportunities was carried out to find potential markets for craft business actors from typical Karo woven cloth in North Sumatra so that they could maximize marketing efforts globally. This research aims to determine the export market potential for Karo handicraft products and find the right strategy in marketing typical Karo handicraft products. The research method used in this research is a qualitative approach, then data collection is carried out through interviews, observation and surveys. The results of data testing show that the potential export markets for Karo craft products are Singapore and then Malaysia, so it is necessary to maximize market opportunities in these countries with appropriate export marketing strategies. Karo craft entrepreneurs need to maximize marketing to export destination countries with strategies that can be implemented starting from online marketing, participating in international exhibitions and events as well as carrying out strategic collaborations.